Analysis of Halal Value Chain Education in Efforts to Develop Halal Tourism Products and Increase Income - Hutabarat, Zuhri Saputra; Masni, Harbeng; Zahar, Erlina; Pratiwi, Heni; Sembiring, Benar; Azizah, Azizah; Andriani, Lili; Rahim, Arif; Tara, Firman (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
The aim of this research is to analyze the halal value chain in developing halal tourism products and increasing the income of Kampoeng Radja in Jambi City. The halal value chain in the sharia economic sector has an important role in economic progress. However, the economic potential has not been exploited optimally. Jambi City, as one of the areas that has potential in developing halal value chains in the halal tourism industry sector, has also not utilized this potential properly. This research is field research with a qualitative approach. This research uses two types of data sources, namely primary data and secondary data. Data collection techniques were carried out using observation, interviews and documentation. The research results show that the halal value chain in developing halal tourism products and increasing the income of Kampoeng Radja in Jambi City still needs improvement, such as tourism assets that are not yet sharia-based, especially culinary delights that do not yet have a halal certificate.